An inductively coupled ultra‐thin, flexible, and passive RF resonator for MRI marking and guiding purposes: Clinical feasibility. Issue 1 (16th November 2017) - Alipour, Akbar; Gokyar, Sayim; Algin, Oktay; Atalar, Ergin; Demir, Hilmi Volkan
Abstract : Purpose: The purpose of this study is to develop a wireless, flexible, ultra‐thin, and passive radiofrequency‐based MRI resonant fiducial marker, and to validate its feasibility in a phantom model and several body regions. Methods: Standard microfabrication processing was used to fabricate the resonant marker. The proposed marker consists of two metal traces in the shape of a square with an edge length of 8 mm, with upper and lower traces connected to each other by a metalized via. A 3T MRI fiducial marking procedure was tested in phantom and ex vivo, and then the marker's performance was evaluated in an MRI experiment using humans. The radiofrequency safety was also tested using temperature sensors in the proximity of the resonator. Results: A flexible resonator with a thickness of 115 μm and a dimension of 8 × 8 mm was obtained. The experimental results in the phantom show that at low background flip angles (6–18°), the resonant marker enables precise and rapid visibility, with high marker‐to‐background contrast and signal‐to‐noise ratio improvement of greater than 10 in the vicinity of the marker. Temperature analysis showed a specific absorption ratio gain of 1.3. Clinical studies further showed a successful biopsy procedure using the fiducial marking functionality of our device. Conclusions: The ultra‐thin and flexible structure of this wireless flexible radiofrequency resonant marker offers effective and safe MR visualization with high feasibility for anatomic marking and guiding at various regions of the body. Magn Reson Med 80:361–370, 2018. © 2017 International Society for Magnetic Resonance in Medicine.